A randomized controlled trial of unresisted vs. heavy resisted sprint training programs: effects on strength, jump, unresisted and resisted sprint performance in youth rugby union players - Zabaloy, S.; Healy, R.; Pereira, L. A.; Tondelli, E.; Tomaghelli, L.; Aparicio, J.; Vega, F.; Medrano, J.; Giráldez, J.; Comyns, T.; Freitas, T. T.; Loturco, I. (Journal of Human Kinetics, 2025)
This study aimed to compare: 1) the effects of a 4-week unresisted vs. resisted sprint training programs (UST and RST with 50% body mass, respectively) on both resisted and unresisted sprint performance; and 2) the effects of these sprint training schemes on various strength-power measures (i.e., one-repetition maximum [1RM] and the isometric squat test (ISqT), eccentric hamstring strength in the Nordic hamstring exercise [NHE], and vertical and horizontal jump distances). Thirty-five under-19 male academy rugby players participated in the study and were randomly assigned to one of the two training groups. Players` unresisted and resisted (50% BM) 30-m sprint performance, squat 1RM, ISqT, NHE, and jump capabilities were tested on different occasions. Only UST produced a significant reduction in unresisted 30-m sprint time (p < 0.05), whereas both groups exhibited significant changes in resisted sprint times at 10 m and 30 m, as well as maximum velocity (p < 0.005; ES: large). Regarding strength measures, RST led to significant increases in ISqT peak force, horizontal jump distance, and NHE strength (p < 0.011; ES: large). Overall, no significant differences were detected between UST and RST in any of the primary or secondary measures after the intervention. Both training methods were equally effective in improving resisted sprint performance in youth male rugby players. Moreover, UST and RST could be effective options for maintaining or even improving various neuromuscular measures (e.g., dynamic-explosive, isometric, and eccentric strength) when lower limb resistance training is reduced during the competitive season due to the congested schedule.